Samarium cobalt permanent magnet and preparation method and application thereof
By adjusting the particle size of the samarium-cobalt permanent magnet material and mixing and processing, the problem of samarium-cobalt permanent magnet is solved, and its bending strength and magnetic properties are improved. The production process is simplified, and the needs of miniaturization, lightweight, high function and high precision are met.
Patent Information
- Application Number
- CN202510277620.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-29
AI Technical Summary
Existing samarium-cobalt permanent magnets are prone to rupture during processing and application, resulting in high manufacturing losses and difficult to meet the needs of miniaturization, lightweight, high functionality and high precision, while improving mechanical properties will reduce magnetic properties.
By adjusting the particle size of the material, a first alloy fine powder with D50 of 4 to 6 μm and a second alloy fine powder with D50 of 0.5 to 1.2 μm were prepared, and the mixture was mixed, and the orientation molding, isostatic pressure, sintering, solid solution and aging treatment were performed to prepare a samarium-cobalt permanent magnet with high flexural strength and basically no degradation of magnetic properties.
On the basis of basically not reducing the magnetic properties of samarium-cobalt permanent magnets, the bending strength is significantly improved, manufacturing losses are reduced, the production process is simplified, and the application flexibility of the product is improved.
Smart Images

Figure BDA0005304702150000151
Abstract
Description
Technical Field
[0001] The invention relates to a samarium cobalt permanent magnet and a preparation method and application thereof, and in particular to a samarium cobalt permanent magnet and a preparation method thereof, and application of ultrafine powder in improving the bending strength of the samarium cobalt permanent magnet without reducing the magnetic properties of the samarium cobalt permanent magnet. Background Art
[0002] SmCo sintered permanent magnet materials have high Curie temperature and magnetic properties, low temperature coefficient and excellent corrosion resistance, which makes them play an irreplaceable role in special application fields such as aerospace, microwave communication and military industry. In recent years, with the development of high technology, the demand for the application of permanent magnet materials under extreme conditions has been increasing.
[0003] Sm2Co 17 The crystal structures of SmCo and SmCo5 do not have sufficient slip systems to cope with plastic deformation, so they are inherently brittle. This makes them prone to breakage during processing and equipment assembly, resulting in high manufacturing losses (20-30%). At the same time, it limits the shapes, sizes and application areas that SmCo magnets can produce, and cannot meet the development needs of permanent magnets in the direction of miniaturization, lightweight, high functionality and high precision. For example, in the field of modern high-precision instrumentation, the manufacturing accuracy standards for magnets continue to rise, and SmCo magnets are brittle and hard in texture. During the processing and actual application stages, they are prone to cracking, edge collapse and even partial shedding. At the same time, the internal stress changes are also significant, affecting the performance of the magnets.
[0004] In the current technological development trend, the mechanical properties of sintered SmCo permanent magnets are becoming increasingly important properties that need to be considered. Existing research on improving the mechanical properties of sintered SmCo permanent magnets mainly focuses on adding second-phase alloys to the material, but while improving its mechanical properties, it often causes a decrease in magnetic properties. In this context, how to effectively improve the mechanical properties of SmCo permanent magnets while taking into account the magnetic properties of SmCo permanent magnets is gradually becoming a key exploration and tackling direction for scientific researchers, material engineers, and experts in related fields.
[0005] CN107316726A discloses a method for preparing a sintered samarium cobalt magnet, comprising: (1) preparing alloy powder; preparing samarium cobalt alloy raw material according to weight percentage, wherein R is added, wherein R is one or more of Ce, Pr, Nd, Gd, Tb, Dy, Ho and Er; smelting, casting and mechanical crushing; and then preparing alloy powder by oxygen-supplemented air flow grinding technology; (2) cleaning, crushing, conventional air flow grinding and fully mixing the scraps and waste materials with similar composition to the alloy powder to prepare auxiliary material powder; (3) mixing, mixing the alloy powder and the auxiliary material powder in proportion to prepare samarium cobalt alloy powder; (4) magnetic field forming and isostatic pressing to prepare green blanks; (5) sintering solid solution and aging treatment to prepare samarium cobalt magnets. The sintered samarium cobalt magnet prepared by the method of the present invention has good mechanical properties and a bending strength greater than 100 MPa. The preparation method reuses leftovers and waste materials by adding rare earth R, so that the obtained sintered samarium cobalt magnet has better mechanical properties.
[0006] CN119274907A discloses a samarium cobalt magnet and a preparation method thereof, which comprises a powder laying and pressing step, wherein samarium cobalt A powder and samarium cobalt B powder are alternately laid to ensure that the bottom layer and the top layer are samarium cobalt B powder, and the particle sizes of samarium cobalt A powder and samarium cobalt B powder are different; the weight of the samarium cobalt A powder is 5wt%-50wt%, and the weight of the samarium cobalt B powder is 95wt%-50wt%. The mechanical properties of the obtained magnet are enhanced. The preparation method is relatively cumbersome, and two powders with different particle sizes need to be laid alternately.
[0007] CN118039275A discloses a samarium cobalt rare earth magnet and a preparation method thereof, the preparation method comprising the following steps: (1) preparing an ingot a from a first part of samarium cobalt alloy raw material; (2) preparing a slab b from a second part of samarium cobalt alloy raw material; (3) preparing an alloy powder A and an alloy powder B from the ingot a and the slab b respectively; (4) mixing the alloy powder A and the alloy powder B to obtain alloy magnetic powder; (5) molding the alloy magnetic powder under an oriented magnetic field, isostatically pressing, and obtaining a green body; (6) performing sintering, solid solution treatment, and aging heat treatment on the green body to obtain a samarium cobalt rare earth magnet. Although the bending strength of the magnet manufactured by the preparation method is relatively high, it involves two smelting processes, which easily leads to uneven performance, and once a quality problem occurs, it is difficult to determine the root cause of the problem, which is not conducive to quality control and improvement. Summary of the invention
[0008] One object of the present invention is to provide a method for preparing a samarium cobalt permanent magnet, which can improve the bending strength of the obtained samarium cobalt permanent magnet without substantially reducing the magnetic properties of the samarium cobalt permanent magnet. Another object of the present invention is to provide a samarium cobalt permanent magnet prepared according to the preparation method as described above. Another object of the present invention is to provide an application of ultrafine powder in improving the bending strength of samarium cobalt permanent magnet without reducing its magnetic properties.
[0009] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0010] In one aspect, the present invention provides a method for preparing a samarium cobalt permanent magnet, comprising the following steps:
[0011] 1) The alloy ingot formed by the raw materials required for the samarium cobalt permanent magnet is crushed and jet milled to obtain D 50 The first alloy fine powder is 4 to 6 μm;
[0012] 2) 15-30 wt% of the first alloy fine powder is taken out, and then the taken out first alloy fine powder is ball-milled to obtain D 50 The second alloy fine powder is 0.5 to 1.2 μm;
[0013] 3) mixing the remaining first alloy fine powder and the second alloy fine powder obtained in step 2) to obtain a mixed powder;
[0014] 4) Orienting and molding the mixed powder and isostatically pressing to obtain a green body; sintering, solid solution and aging the green body to obtain a samarium cobalt permanent magnet.
[0015] According to the preparation method of the present invention, preferably, in step 1), the required raw materials are prepared according to the composition of the samarium cobalt permanent magnet; the samarium cobalt permanent magnet has the following composition:
[0016] Based on the total mass of the samarium cobalt permanent magnet, Sm 25-27wt%, Co 48-51wt%, Fe 15-18wt%, Cu 4-6wt%, and Zr 2-3wt%.
[0017] According to the preparation method of the present invention, preferably, in step 1), the raw materials required for the samarium cobalt permanent magnet are melted and cast in a vacuum induction melting furnace to form an alloy ingot; the alloy ingot is first crushed for the first time using a jaw crusher, and then crushed for the second time using a medium crusher to obtain medium-crushed particles; after the second crushing is completed, a lubricant and an antioxidant are added to the medium-crushed particles and mixed, and then air flow milling is performed to obtain a first alloy fine powder.
[0018] According to the preparation method of the present invention, preferably, the amount of lubricant added is 0.03-0.04 wt% of the mass of the medium-broken particles, and the amount of antioxidant added is 0.04-0.05 wt% of the mass of the medium-broken particles.
[0019] According to the preparation method of the present invention, preferably, the oxygen content is controlled below 100 ppm during air flow milling.
[0020] According to the preparation method of the present invention, preferably, in step 2), the taken out 15-30 wt% of the first alloy fine powder is ball-milled in an inert atmosphere using a planetary ball mill.
[0021] According to the preparation method of the present invention, preferably, in step 3), the remaining first alloy fine powder and the second alloy fine powder are mixed in a mixer for 1 to 2 hours to obtain a mixed powder.
[0022] According to the preparation method of the present invention, preferably:
[0023] In step 4), the magnetic field intensity during orientation molding is 1.6 to 2 T; the isostatic pressing pressure is 260 to 280 MPa;
[0024] In step 4), the sintering temperature is 1150-1250° C., and the sintering time is 1-3 hours; the solution temperature is 1140-1190° C., and the solution time is 1-5 hours; the aging treatment temperature is 800-850° C., and the aging treatment time is 10-15 hours.
[0025] On the other hand, the present invention also provides a samarium cobalt permanent magnet, which is prepared according to the preparation method as described above.
[0026] In another aspect, the present invention also provides an application of ultrafine powder in improving the bending strength of samarium cobalt permanent magnets without reducing their magnetic properties, wherein the ultrafine powder is obtained by sequentially casting, crushing, jet milling and ball milling the raw materials required for samarium cobalt permanent magnets. 50 The method comprises the following steps:
[0027] 1) The alloy ingot formed by the raw materials required for the samarium cobalt permanent magnet is crushed and jet milled to obtain D 50 The first alloy fine powder is 4 to 6 μm;
[0028] 2) taking out a portion of the first alloy fine powder, and then ball milling the taken out first alloy fine powder to obtain D 50 The second alloy fine powder is 0.5 to 1.2 μm; wherein the second alloy fine powder is ultrafine powder;
[0029] 3) mixing the first alloy fine powder and the second alloy fine powder obtained in step 2) to obtain a mixed powder; wherein, based on the mass of the mixed powder, the mass proportion of the first alloy fine powder is 70-85wt%, and the mass proportion of the second alloy fine powder is 15-30wt%;
[0030] 4) Orienting and molding the mixed powder and isostatically pressing to obtain a green body; sintering, solid solution and aging the green body to obtain a samarium cobalt permanent magnet.
[0031] The preparation method of the present invention can improve the bending strength of the obtained samarium cobalt permanent magnet without substantially reducing the magnetic properties of the samarium cobalt permanent magnet. The preparation method of the present invention does not need to add other elements, and the composition of the obtained samarium cobalt permanent magnet will not change. In addition, the preparation method of the present invention does not need to alternately overlap and lay the first alloy fine powder and the second alloy fine powder, and only needs to mix them. The preparation method of the present invention does not need to be formulated according to multiple formulas, does not involve multiple smelting processes, and only needs to be formulated according to the chemical formula of the samarium cobalt permanent magnet, and the production process is easy to control. This is more conducive to the operation of the operator during production. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0033] The inventors of the present application have developed a preparation method that does not change the composition of the samarium cobalt permanent magnet, only adjusts the particle size of the material, and only mixes two alloy fine powders of different particle sizes without alternating and paving them to enhance the mechanical properties of the samarium cobalt permanent magnet and basically does not reduce its magnetic properties. This method has positive significance for the sintering preparation of samarium cobalt permanent magnet materials.
[0034] The "remanent magnetism" mentioned in the present invention refers to the value of the magnetic flux density corresponding to the point where the magnetic field intensity is zero on the saturation hysteresis loop, and the unit is Tesla (T) or Gauss (Gs).
[0035] The "coercive force" mentioned in the present invention, also known as intrinsic coercive force, refers to the magnetic field intensity when the magnetic field is monotonically reduced to zero and then increased in the opposite direction from the saturated magnetization state of the magnet, so that the magnetization intensity decreases to zero along the saturation hysteresis loop, and the unit is Oersted (Oe) or Ampere / meter (A / m). 1Oe = 79.6A / m.
[0036] The "maximum magnetic energy product" mentioned in the present invention refers to the product of the magnetic induction intensity (B) and the magnetic field intensity (H) at any point on the demagnetization curve of the magnet, where the energy density when the product of B and H reaches the maximum value is expressed in mega-gaoseres (MGOe) or joules / cubic meter (J / m 3 ). 1MGOe≈7.96kJ / m 3 .
[0037] In the present invention, D 50 Also called median diameter or median particle size, it is a statistic that represents particle size distribution. Its specific meaning is as follows: In the particle size distribution of a particle group, the particles are sorted by particle size. The particle size value corresponding to the cumulative particle size distribution percentage reaching 50% is called D 50That is to say, among all the particles, 50% of the particles have a particle size smaller than this value, and the other 50% of the particles have a particle size larger than this value.
[0038] <Method for preparing samarium cobalt permanent magnet>
[0039] The method for preparing the samarium cobalt permanent magnet of the present invention comprises the following steps: (1) a preparation step of a first alloy fine powder; (2) a preparation step of a second alloy fine powder; (3) a mixing step; and (4) a molding and heat treatment step. In addition, a batching step is also included. The preparation step of the first alloy fine powder comprises a smelting ingot step, a crushing step, and a jet milling step. The following is a detailed description.
[0040] Ingredients Steps
[0041] The raw materials required for the samarium cobalt permanent magnet of the present invention include Sm, Co, Fe, Cu and Zr.
[0042] The required raw materials are prepared according to the composition of the samarium cobalt permanent magnet, which has the following composition: based on the total mass of the samarium cobalt permanent magnet, Sm 25-27wt%, Co 48-51wt%, Fe 15-18wt%, Cu 4-6wt%, and Zr 2-3wt%.
[0043] Based on the total mass of the samarium cobalt permanent magnet, the Sm content is preferably 25.3-26.5wt%, more preferably 25.3-26wt%. The Fe content is preferably 15.5-18wt%, more preferably 16.5-17.5wt%. The Cu content is preferably 4.5-6wt%, more preferably 4.7-5.9wt%. The Zr content is preferably 2.1-2.8wt%, more preferably 2.3-2.6wt%. Co is the balance.
[0044] In some specific embodiments, the raw materials required for the samarium cobalt permanent magnet are prepared according to the composition of the samarium cobalt permanent magnet as described above. Considering that Sm will volatilize during the smelting process, 1-2 wt% more can be weighed during the preparation. The purity of each metal element is greater than or equal to 99.9%.
[0045] Preparation steps of the first alloy fine powder
[0046] The preparation steps of the first alloy fine powder include a melting ingot step, a crushing step and a jet milling step. The alloy ingot formed by the raw materials required for the samarium cobalt permanent magnet is crushed and jet milled to obtain D 50 The first alloy fine powder is 4 to 6 μm. This is conducive to obtaining samarium cobalt permanent magnets with better magnetic properties and higher bending strength.
[0047] In the present invention, the step of melting and casting the ingot comprises: placing the prepared raw materials in a vacuum induction melting furnace for melting and casting to obtain an alloy ingot. The melting temperature and time can be those known in the art.
[0048] The crushing step includes a coarse crushing and a medium crushing step, specifically comprising: first crushing the alloy ingot with a jaw crusher to obtain coarse crushed particles; then crushing the coarse crushed particles with a medium crusher to obtain medium crushed particles. The particle size of the coarse crushed particles can be 5 to 50 mm, preferably 6 to 45 mm, and more preferably 6 to 40 mm. The particle size of the medium crushed particles can be less than 0.4 mm, for example, 0.05 to 0.4 mm.
[0049] In the present invention, the jet milling step comprises: after the second crushing is completed, a lubricant and an antioxidant are added to the medium-crushed particles and mixed, and then the first alloy fine powder is obtained by jet milling. The lubricant can be selected from those known in the art, preferably selected from at least one of zinc stearate, calcium stearate, magnesium stearate, erucic acid amide, oleic acid amide, and polyethylene wax, and more preferably zinc stearate. The amount of lubricant added is 0.03-0.04wt% of the mass of the medium-crushed particles, preferably 0.032-0.038wt%, and more preferably 0.035-0.037wt%. The antioxidant can be selected from those known in the art, preferably selected from one of phosphite, polyethylene oxide olefin ether, and zinc stearate, and more preferably phosphite. The amount of antioxidant added is 0.04-0.05wt% of the mass of the medium-crushed particles, preferably 0.042-0.048wt%, and more preferably 0.045-0.047wt%.
[0050] The oxygen content during jet milling is below 100 ppm. 50 In certain specific embodiments, the D 50 In some other specific embodiments, the D 50 5~6μm.
[0051] Preparation steps of the second alloy fine powder
[0052] 15-30 wt% of the first alloy fine powder is taken out, and then the taken out first alloy fine powder is ball-milled to obtain D 50 The invention finds that the bending strength of the prepared samarium cobalt permanent magnet can be significantly improved, and the magnetic properties remain basically unchanged, by mixing the second alloy fine powder with a smaller particle size obtained by ball milling with the first alloy fine powder with a larger particle size at a specific mass ratio.
[0053] In certain embodiments, the first alloy fine powder of 15 to 30 wt% taken out is ball-milled using a planetary ball mill under an inert atmosphere. The inert atmosphere can be an atmosphere formed by an inert gas or nitrogen. The nitrogen can be high-purity nitrogen. The inert gas can be selected from at least one of helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe). Preferably, the inert gas is selected from at least one of helium, neon, and argon; more preferably, the inert gas is selected from at least one of helium and argon.
[0054] In the present invention, the manufacturer and model of the planetary ball mill are not particularly limited, and those known in the art can be used.
[0055] According to one embodiment of the present invention, the particle size of the grinding balls used in the planetary ball mill can be 5 mm. The ball-to-material ratio (i.e., the mass ratio of the grinding balls to the first alloy fine powder to be ball-milled) can be 6:1 to 4:1, preferably 5:1 to 4:1. The ball milling speed can be 100 to 400 r / min, preferably 200 to 350 r / min, and more preferably 250 to 320 r / min. The ball milling time can be 1 to 5 hours, preferably 2 to 4 hours, and more preferably 2 to 3 hours.
[0056] In the present invention, the planetary ball mill can be placed in a glove box under nitrogen protection to perform ball milling to obtain the second alloy fine powder without worrying about the powder being too fine and easily catching fire, thereby eliminating potential safety hazards.
[0057] In the present invention, the particle size D of the obtained second alloy fine powder is 50 The thickness may be 0.5 to 1.2 μm, preferably 0.5 to 1.1 μm, and more preferably 0.6 to 1.0 μm.
[0058] According to a specific embodiment of the present invention, the particle size D of the second alloy fine powder is 50 According to another specific embodiment of the present invention, the particle size D of the second alloy fine powder is 50 It is 0.6~0.8μm.
[0059] Mixing Steps
[0060] The remaining first alloy fine powder and the obtained second alloy fine powder are mixed to obtain a mixed powder. That is, based on the mass of the mixed powder, the mass ratio of the first alloy fine powder is 70-85wt%, and the mass ratio of the second alloy fine powder is 15-30wt%. The present invention finds that if the mass ratio of the two is not within the scope of the present invention, the magnetic properties and bending strength of the obtained samarium cobalt permanent magnet cannot be taken into account.
[0061] Based on the mass of the mixed powder, the mass proportion of the second alloy fine powder is preferably 15-28wt%, more preferably 15-25wt%. For example, it can be 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%.
[0062] In the present invention, the remaining first alloy fine powder and the second alloy fine powder are mixed in a mixer for 1 to 2 hours to obtain a mixed powder. The mixing time is preferably 1 to 1.5 hours. In this way, the mixture can be mixed evenly. The mixer can be a three-dimensional mixer. The three-dimensional mixer can be those commercially available, and its source is not particularly limited herein.
[0063] Forming and heat treatment steps
[0064] The mixed powder is oriented and molded, and isostatically pressed to obtain a green body; the green body is sintered, solid-solution treated, and aging treated to obtain a samarium cobalt permanent magnet. In this way, a samarium cobalt permanent magnet with stable magnetic properties can be obtained.
[0065] The magnetic field intensity during the orientation molding of the mixed powder can be 1.6 to 2 T, preferably 1.7 to 2 T, and more preferably 1.7 to 1.8 T. After the orientation molding, a compact is obtained, and the compact is isostatically pressed to obtain a green compact. Isostatic pressing is cold isostatic pressing, which is a technology known in the art and will not be described in detail here. The pressure of isostatic pressing can be 260 to 280 MPa, preferably 265 to 275 MPa, and more preferably 270 to 275 MPa.
[0066] The obtained green body is placed in a vacuum sintering furnace for heat treatment to obtain a samarium cobalt permanent magnet. The vacuum degree during heat treatment is less than 10Pa, preferably less than or equal to 5Pa, more preferably less than or equal to 0.1Pa, and more preferably less than or equal to 0.01Pa. Specifically, the heat treatment includes sintering, solid solution and aging treatment steps in sequence. Among them, the sintering temperature can be 1150-1250℃, preferably 1180-1230℃, and more preferably 1200-1225℃. The sintering time can be 1-3h, preferably 2-3h. The solid solution temperature can be 1140-1190℃, preferably 1160-1190℃, and more preferably 1170-1190℃. The solid solution time can be 1-5h, preferably 1-4h, and more preferably 1-3h. The temperature of aging treatment can be 800-850℃, preferably 820-850℃, and more preferably 820-840℃. The aging treatment time may be 10 to 15 hours, preferably 10 to 14 hours, and more preferably 10 to 13 hours, which is conducive to obtaining samarium cobalt permanent magnets with uniform and stable magnetic properties.
[0067] After aging treatment, the temperature can be naturally lowered to below 50° C. in the furnace to obtain samarium cobalt permanent magnets.
[0068] According to a specific embodiment of the present invention, the method for preparing the samarium cobalt permanent magnet of the present invention comprises the following steps:
[0069] 1) The alloy ingot formed by the raw materials required for the samarium cobalt permanent magnet is crushed and jet milled to obtain D 50 The first alloy fine powder is 4 to 6 μm;
[0070] 2) 15-25 wt% of the first alloy fine powder is taken out, and then the taken out first alloy fine powder is ball-milled to obtain D 50 The second alloy fine powder is 0.5 to 1.2 μm;
[0071] 3) mixing the remaining first alloy fine powder and the second alloy fine powder obtained in step 2) to obtain a mixed powder;
[0072] 4) Orienting and molding the mixed powder and isostatically pressing to obtain a green body; sintering, solid solution and aging the green body to obtain a samarium cobalt permanent magnet.
[0073] <Samarium Cobalt Permanent Magnets>
[0074] The samarium cobalt permanent magnet obtained by the preparation method as described above has a remanence greater than 11 kGs, preferably greater than or equal to 11.1 kGs; a coercive force greater than 32.5 kOe, preferably greater than or equal to 32.6 kOe; and a maximum magnetic energy product greater than 28.8 MGOe, preferably greater than or equal to 28.9 MGOe. The bending strength of the obtained samarium cobalt permanent magnet is greater than 127 MPa, preferably greater than or equal to 130 MPa, and more preferably greater than or equal to 132 MPa.
[0075] <Purpose>
[0076] The present invention also provides an application of ultrafine powder in improving the bending strength of samarium cobalt permanent magnets without reducing their magnetic properties. The ultrafine powder is obtained by sequentially casting, crushing, jet milling and ball milling the raw materials required for samarium cobalt permanent magnets. 50 The method comprises the following steps:
[0077] 1) The alloy ingot formed by the raw materials required for the samarium cobalt permanent magnet is crushed and jet milled to obtain D 50 The first alloy fine powder is 4 to 6 μm;
[0078] 2) taking out a portion of the first alloy fine powder, and then ball milling the taken out first alloy fine powder to obtain D 50 The second alloy fine powder is 0.5 to 1.2 μm; wherein the second alloy fine powder is ultrafine powder;
[0079] 3) mixing the first alloy fine powder and the second alloy fine powder obtained in step 2) to obtain a mixed powder; wherein, based on the mass of the mixed powder, the mass proportion of the first alloy fine powder is 70-85wt%, and the mass proportion of the second alloy fine powder is 15-30wt%;
[0080] 4) Orienting and molding the mixed powder and isostatically pressing to obtain a green body; sintering, solid solution and aging the green body to obtain a samarium cobalt permanent magnet.
[0081] In step 2), taking out a portion of the first alloy fine powder means taking out 15-30 wt % of the first alloy fine powder. Detailed process parameters and steps are as mentioned above and will not be described here.
[0082] <Analysis Method>
[0083] The magnetic properties were tested using a Hirst permanent magnet pulse measuring instrument.
[0084] Bending strength test: Use a universal testing machine to perform a three-point bending test.
[0085] In the following examples and comparative examples,
[0086] The lubricant used is zinc stearate and the antioxidant used is phosphite.
[0087] Example 1
[0088] The raw materials required for the samarium cobalt permanent magnet are prepared according to the following specific composition: based on the total mass of the samarium cobalt permanent magnet, Sm 25.3wt%, Co 49.5wt%, Fe 17.3wt%, Cu 5.6wt%, and Zr 2.3wt%.
[0089] The prepared raw materials are melted and cast in a vacuum induction melting furnace to obtain alloy ingots.
[0090] The alloy ingot is first crushed by a jaw crusher, and then crushed by a medium crusher to obtain medium crushed particles with a particle size of less than 0.4 mm. After the second crushing, 0.035 wt% lubricant and 0.045 wt% antioxidant are added to the material tank containing the medium crushed particles, and mixed evenly with a mixer. Then, the jet mill is used, and the oxygen content of the jet mill is controlled below 100 ppm to make the particle size D 50 The particle size of the powder is controlled at 4 to 6 μm, and the fine powder ground by the jet mill is mixed in a three-dimensional mixer for 2 hours to enhance the uniformity of the powder particle size to obtain the first alloy fine powder.
[0091] 15 wt% of the first alloy fine powder was taken out, and the first alloy fine powder was further ball-milled for 2 h using a planetary ball mill under nitrogen protection to obtain D 50The second alloy fine powder is controlled to be 0.5-1.2 μm. The obtained second alloy fine powder is mixed with the remaining first alloy fine powder (85 wt%) in a three-dimensional mixer for 2 hours to obtain a mixed powder.
[0092] The mixed powder is pressed into a 60mm×50mm×50mm block in an orientation press with a magnetic field strength of 2T to obtain a compact. The compact is then cold isostatically pressed at a pressure of 270MPa. The green compact after cold isostatic pressing is placed in a vacuum sintering furnace, sintered at 1210℃ for 2h, and then solutionized at 1180℃ for 2h. The solutionized blank is aged at 820℃ for 11h, then cooled to below 50℃ and taken out of the furnace. A samarium cobalt permanent magnet is obtained.
[0093] The performance test of the samarium cobalt permanent magnet obtained in this embodiment is shown in Table 1.
[0094] Example 2
[0095] Except for the following parameters and settings, the rest are the same as Example 1:
[0096] In this embodiment, 20 wt% of the first alloy fine powder was taken out, and the taken out first alloy fine powder was further ball-milled for 2 h using a planetary ball mill under nitrogen protection to obtain D 50 The second alloy fine powder is controlled to be 0.5-1.2 μm. The obtained second alloy fine powder is mixed with the remaining first alloy fine powder (80 wt%) in a three-dimensional mixer for 2 hours to obtain a mixed powder.
[0097] The performance test of the samarium cobalt permanent magnet obtained in this embodiment is shown in Table 1.
[0098] Example 3
[0099] Except for the following parameters and settings, the rest are the same as Example 1:
[0100] In this embodiment, 25 wt% of the first alloy fine powder was taken out, and the taken out first alloy fine powder was further ball-milled for 2 h using a planetary ball mill under nitrogen protection to obtain D 50 The second alloy fine powder is controlled to be 0.5-1.2 μm. The obtained second alloy fine powder is mixed with the remaining first alloy fine powder (75 wt%) in a three-dimensional mixer for 2 hours to obtain a mixed powder.
[0101] The performance test results of the samarium cobalt permanent magnet obtained in this embodiment are shown in Table 1.
[0102] Comparative Example 1
[0103] The raw materials required for the samarium cobalt permanent magnet are prepared according to the following specific composition: based on the total mass of the samarium cobalt permanent magnet, Sm25.3wt%, Co 49.5wt%, Fe 17.3wt%, Cu 5.6wt%, and Zr2.3wt%.
[0104] The prepared raw materials are melted and cast in a vacuum induction melting furnace to obtain alloy ingots.
[0105] The alloy ingot is first crushed by a jaw crusher, and then crushed by a medium crusher to obtain medium crushed particles with a particle size of less than 0.4 mm. After the second crushing, 0.035 wt% lubricant and 0.045 wt% antioxidant are added to the material tank containing the medium crushed particles, and mixed evenly with a mixer. Then, the jet mill is used, and the oxygen content of the jet mill is controlled below 100 ppm to make the particle size D 50 The particle size of the powder is controlled at 4 to 6 μm, and the fine powder ground by the jet mill is mixed in a three-dimensional mixer for 2 hours to enhance the uniformity of the powder particle size to obtain the first alloy fine powder.
[0106] The first alloy fine powder is pressed into a 60mm×50mm×50mm block in an orientation press with a magnetic field strength of 2T to obtain a compact. The compact is then cold isostatically pressed at a pressure of 270MPa. The green compact after cold isostatic pressing is placed in a vacuum sintering furnace, sintered at 1210℃ for 2h, and then solutionized at 1180℃ for 2h. The solid solution blank is aged at 820℃ for 11h, then cooled to below 50℃ and taken out of the furnace. A samarium cobalt permanent magnet is obtained.
[0107] The performance test results of the samarium cobalt permanent magnet obtained in this comparative example are shown in Table 1.
[0108] Comparative Example 2
[0109] Except for the following parameters and settings, the rest are the same as Example 1:
[0110] In this embodiment, 5 wt% of the first alloy fine powder was taken out, and the first alloy fine powder was further ball-milled for 2 h using a planetary ball mill under nitrogen protection to obtain D 50 The second alloy fine powder is controlled to be 0.5-1.2 μm. The obtained second alloy fine powder is mixed with the remaining first alloy fine powder (95 wt%) in a three-dimensional mixer for 2 hours to obtain a mixed powder.
[0111] The performance test results of the samarium cobalt permanent magnet obtained in this comparative example are shown in Table 1.
[0112] Comparative Example 3
[0113] Except for the following parameters and settings, the rest are the same as Example 1:
[0114] In this embodiment, 35 wt% of the first alloy fine powder was taken out, and the taken out first alloy fine powder was further ball-milled for 2 h using a planetary ball mill under nitrogen protection to obtain D 50 The second alloy fine powder is controlled to be 0.5-1.2 μm. The obtained second alloy fine powder is mixed with the remaining first alloy fine powder (65 wt%) in a three-dimensional mixer for 2 hours to obtain a mixed powder.
[0115] The performance test results of the samarium cobalt permanent magnet obtained in this comparative example are shown in Table 1.
[0116] Table 1
[0117]
[0118] From the comparison between the embodiments and comparative example 1, it can be seen that the bending strength of the samarium cobalt permanent magnet obtained by the preparation method of the present invention is significantly improved, and the magnetic properties (including remanence, coercive force, and maximum magnetic energy product) are basically not reduced. Even the coercive force of the samarium cobalt permanent magnets of embodiments 2 and 3 is better than the coercive force of the samarium cobalt permanent magnet of comparative example 1.
[0119] As can be seen from the table, the bending strength and magnetic properties of the magnet obtained in Comparative Example 2 are both reduced. Although the bending strength of the magnet in Comparative Example 3 is relatively high, its coercive force and maximum magnetic energy product are both reduced. Therefore, by comparing the embodiment with Comparative Examples 2 and 3, it can be seen that only by controlling the mass ratio of the second alloy fine powder to the first alloy fine powder within a specific range can the magnetic properties and bending strength of the obtained samarium cobalt permanent magnet be taken into account.
[0120] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a samarium cobalt permanent magnet, characterized in that: The steps include: 1) The alloy ingot formed by the raw materials required for the samarium cobalt permanent magnet is crushed and jet milled to obtain D 50 The first alloy fine powder is 4 to 6 μm; 2) 15-30 wt% of the first alloy fine powder is taken out, and then the taken out first alloy fine powder is ball-milled to obtain D 50 The second alloy fine powder is 0.5 to 1.2 μm; 3) mixing the remaining first alloy fine powder and the second alloy fine powder obtained in step 2) to obtain a mixed powder; 4) Orienting and molding the mixed powder and isostatically pressing to obtain a green body; sintering, solid solution and aging the green body to obtain a samarium cobalt permanent magnet.
2. The preparation method according to claim 1, characterized in that: In step 1), the required raw materials are prepared according to the composition of the samarium cobalt permanent magnet; the samarium cobalt permanent magnet has the following composition: Based on the total mass of the samarium cobalt permanent magnet, Sm 25-27wt%, Co 48-51wt%, Fe 15-18wt%, Cu 4-6wt%, and Zr 2-3wt%.
3. The preparation method according to claim 1, characterized in that: In step 1), the raw materials required for the samarium cobalt permanent magnet are melted and cast in a vacuum induction melting furnace to form an alloy ingot; the alloy ingot is first crushed by a jaw crusher, and then crushed by a medium crusher for a second time to obtain medium-crushed particles; after the second crushing is completed, a lubricant and an antioxidant are added to the medium-crushed particles and mixed, and then air flow milling is performed to obtain a first alloy fine powder.
4. The preparation method according to claim 3, characterized in that: The amount of lubricant added is 0.03-0.04wt% of the mass of the medium-broken particles, and the amount of antioxidant added is 0.04-0.05wt% of the mass of the medium-broken particles.
5. The preparation method according to claim 3, characterized in that: The oxygen content is controlled below 100 ppm during air flow milling.
6. The preparation method according to claim 1, characterized in that: In step 2), 15 to 30 wt % of the first alloy fine powder is ball-milled in an inert atmosphere using a planetary ball mill.
7. The preparation method according to claim 1, characterized in that: In step 3), the remaining first alloy fine powder and the second alloy fine powder are mixed in a mixer for 1 to 2 hours to obtain a mixed powder.
8. The preparation method according to claim 1, characterized in that: In step 4), the magnetic field intensity during orientation molding is 1.6 to 2 T; the isostatic pressing pressure is 260 to 280 MPa; In step 4), the sintering temperature is 1150-1250° C., and the sintering time is 1-3 hours; the solution temperature is 1140-1190° C., and the solution time is 1-5 hours; the aging treatment temperature is 800-850° C., and the aging treatment time is 10-15 hours.
9. A samarium cobalt permanent magnet, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 8.
10. An application of ultrafine powder in improving the bending strength of samarium cobalt permanent magnets without reducing their magnetic properties, characterized in that: The ultrafine powder is obtained by sequentially casting, crushing, jet milling and ball milling the raw materials required for samarium cobalt permanent magnets. 50 The method comprises the following steps: 1) The alloy ingot formed by the raw materials required for the samarium cobalt permanent magnet is crushed and jet milled to obtain D 50 The first alloy fine powder is 4 to 6 μm; 2) taking out a portion of the first alloy fine powder, and then ball milling the taken out first alloy fine powder to obtain D 50 A second alloy fine powder of 0.5 to 1.2 μm; wherein the second alloy fine powder is the ultrafine powder; 3) mixing the first alloy fine powder and the second alloy fine powder obtained in step 2) to obtain a mixed powder; wherein, based on the mass of the mixed powder, the mass proportion of the first alloy fine powder is 70-85wt%, and the mass proportion of the second alloy fine powder is 15-30wt%; 4) Orienting and molding the mixed powder and isostatically pressing to obtain a green body; sintering, solid solution and aging the green body to obtain a samarium cobalt permanent magnet.
Citation Information
Patent Citations
Preparation method of sintered samarium-cobalt magnet
CN107316726A
Samarium cobalt rare earth magnet and preparation method thereof
CN118039275A
Samarium-cobalt magnet with high mechanical property and preparation method of samarium-cobalt magnet
CN119274907A
Cited By
Samarium-cobalt permanent magnet material and preparation method and application thereof
CN120452971A
Samarium cobalt permanent magnet material and preparation method thereof
CN120854157A
Large-orientation-size samarium-cobalt magnet and preparation method thereof
CN121394089A